International history of city development - Gutkind, E.A. (New York : The Free press, 1964)
Planificación urbana en Europa, desde la antigüedad hasta el Siglo XIX. Contenido: -v.1: Europa central. -v.2: Los Alpes y Península Escandinava. -v.3: España y Portugal. -v.4: Italia y Grecia. -v.5: Francia y Bélgica.
T.1 . Urban development in Central Europe -- T.2 . Urban development in the Alpine and Scandinavian countries -- T.3 . Urban development in Southern Europe: Spain and Portugal -- T.4 . Urban development in Southern Europe: Italy and Greece -- T.5 . Urban development in Western Europe: France and Belgium
Keywords: URBANISMO; HISTORIA; EUROPA; CIUDADES; PLANIFICACION URBANA; DESARROLLO URBANO; CIUDAD